2010
DOI: 10.1074/jbc.m109.044271
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interactions Regulate Targeting of Calcium Channel β Subunits and Membrane Expression of α1 Subunits in Cultured Hippocampal Neurons

Abstract: Auxiliary ␤ subunits modulate current properties and mediate the functional membrane expression of voltage-gated Ca 2؉ channels in heterologous cells. In brain, all four ␤ isoforms are widely expressed, yet little is known about their specific roles in neuronal functions. Here, we investigated the expression and targeting properties of ␤ subunits and their role in membrane expression of Ca V 1.2 ␣ 1 subunits in cultured hippocampal neurons. Quantitative reverse transcription-PCR showed equal expression, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 68 publications
4
81
0
2
Order By: Relevance
“…S5). Membrane expression of Ca V 1.2 in cultured hippocampal neurons was also disrupted after mutation of the key tryptophan residue to alanine (58). Furthermore, double mutations in the same region completely eradicated the Ca V ␤3 stimulation of Fig.…”
Section: Camentioning
confidence: 80%
“…S5). Membrane expression of Ca V 1.2 in cultured hippocampal neurons was also disrupted after mutation of the key tryptophan residue to alanine (58). Furthermore, double mutations in the same region completely eradicated the Ca V ␤3 stimulation of Fig.…”
Section: Camentioning
confidence: 80%
“…4). We also examined the ubiquitination of a mutant Cav1.2 calcium channel construct that cannot associate with the Cavβ subunit (HACav1.2 W440A ) 24,25 . The mutant channel showed robust ubiquitination irrespective of the coexpression of Cavβ 1b (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed by Obermair et al 14 that the selective targeting of Ca V β subunits to neuronal terminals depends on their association with specific Ca V α 1 subunits that are themselves selectively targeted and this could form an alternative hypothesis for the targeting of the Ca V β 2 subunit to MNC terminals. These authors suggested that Ca V β 2 may be slightly more likely to associate with somatodendritic Ca V 1.2 channels whereas Ca V β 4 may be more likely to interact with presynaptic Ca V channels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study of the distribution of fluorescently labeled Ca V β subunits expressed in cultured hippocampal neurons found that all Ca V β subunits accumulate in synaptic terminals, 14 which led the authors to conclude that Ca V β subunits do not possess targeting properties.…”
mentioning
confidence: 89%